Insect Biodiversity in Organic and Non-Organic Rice Ecosystem in The District of Bantul - Eka Armi Ovawanda; Witjaksono Witjaksono; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2016)
Measuring biodiversity of insects is an essential part in management concept of insect pest populations based on ecology. This study examined the index of insect biodiversity by measuring species richness, species evenness and heterogeneity in organic and non-organic rice farming ecosystem. The sampling was conducted during the planting season of April–May 2015 and October–November 2015 at 44, 52 and 66 days after rice transplanting (DAT). High number of species richness (7 to 13 species) was found in the non-organic rice field (April–May 2015). In contrast, high number of species richness (22 to 33 species) was found in the organic rice field (October–November 2015). The species evenness and heterogeneity in the organic farming were generally higher than these in the non-organic rice in the both of planting season April–May 2015 and October–November 2015. Overall, the organic rice farming ecosystem can increase species richness, species evenness and heterogeneity of insect. INTISARI Mengukur biodiversitas serangga adalah salah satu bagian penting dalam konsep pengelolaan populasi serangga hama berbasis ekologi. Penelitian ini mengkaji indeks biodiversitas serangga dengan mengukur kekayaan spesies (species richness), kemerataan spesies (species evenness), dan keanekaragaman/kelimpahan spesies (heterogenity) pada sistem budidaya padi organik dan non-organik. Pengambilan sampel diperoleh pada saat musim tanam April–Mei 2015 dan musim tanam Oktober–November 2015 di 44, 52, dan 66 hari setelah tanam. Total kekayaan spesies tertinggi (7–13 spesies) ditemukan di lahan padi non-organik (April–Mei 2015). Sebaliknya, total kekayaan spesies (22–33 spesies) ditemukan di lahan padi organik (Oktober–November 2015). Kemerataan spesies dan heterogenitas di lahan padi organik secara umum lebih tinggi dibanding di padi non-organik pada kedua musim tanam April–Mei 2015 dan Oktober–November 2015. Secara keseluruhan, sistem budidaya di ekosistem padi organik dapat meningkatkan kekayaan spesies, kemerataan spesies, dan heterogenitas serangga.